2017
DOI: 10.3847/1538-4357/aa78a9
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Circumnuclear Environs of Centaurus A. III. An Inner Molecular Ring, Nuclear Shocks, and the CO to Warm H2 Interface

Abstract: We present the distribution and kinematics of the molecular gas in the circumnuclear disk (CND, 400 pc × 200 pc) of Centaurus A with resolutions of ∼5 pc (0. 3) and shed light onto the mechanism feeding the Active Galactic Nucleus (AGN) using CO(3-2), HCO + (4-3), HCN(4-3), and CO(6-5) observations obtained with ALMA. Multiple filaments or streamers of tens to a hundred parsec scale exist within the CND, which form a ring-like structure with an unprojected diameter of 9 × 6 (162 pc × 108 pc) and a position ang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 128 publications
(235 reference statements)
8
41
0
Order By: Relevance
“…It is worth noting that the velocity field of the inner region of the CND seems to twist in the HCO + (1 − 0) moment 1 map ( Figure 5). This warping appears to decrease the position angle of the inner CND, consistent with the H 2 velocity map of Neumayer et al (2007) and CO maps of Espada et al (2017). However, in the H 2 velocity map, there appears to be another warp further in, not sampled by our data (due to the absorption).…”
Section: Molecular Gas Kinematicssupporting
confidence: 82%
See 2 more Smart Citations
“…It is worth noting that the velocity field of the inner region of the CND seems to twist in the HCO + (1 − 0) moment 1 map ( Figure 5). This warping appears to decrease the position angle of the inner CND, consistent with the H 2 velocity map of Neumayer et al (2007) and CO maps of Espada et al (2017). However, in the H 2 velocity map, there appears to be another warp further in, not sampled by our data (due to the absorption).…”
Section: Molecular Gas Kinematicssupporting
confidence: 82%
“…The outer portions of the CND for these transitions are coincident with the edges of the CND that are seen in 13 CO(2 − 1). Regions C and D are most likely composed of a combination of nuclear filaments and the nuclear ring structure (Espada et al 2017).…”
Section: Molecular Gas Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Morganti 2010 for a review). Interestingly, recent ALMA observations of Centaurus A (Espada et al 2017), reveal a clumpy circumnuclear disk of molecular gas in its innermost 500 pc. In the centre of the disk, there is a lack of CO gas, while the warm H 2 is detected down to small radii (r 10 pc).…”
Section: Discussionmentioning
confidence: 99%
“…Indications that chaotic cold accretion can fuel an AGN have been found also in a handful of other sources. For example, in Centaurus A (Espada et al 2017), NGC 5044 (David et al 2014;Russell et al 2016;David et al 2017) and PKS 2322-12 (Tremblay et al 2016) cold gas clouds with non circular orbits are found in proximity of the AGN. While in NGC 3115 (Wong et al 2013) and M 87 (Russell et al 2015) similar clouds are likely condensating from the hot circumnuclear environment.…”
Section: Discussionmentioning
confidence: 99%